Marketing Effectiveness in Islamic Financial Cooperative: A Case Study - Zulfi Bagja Nugraha, Reza Ashari Nasution (ITB, 2010)
Cooperative is a modal of kinship economic form in Indonesia which supported by national constitution. As a "Muslim majority country" value of Islamic religion brought to every segment of life, including cooperative as an economic form based on kinship. Islamic financial cooperative was a role model of religous based of alternative kinship economic form, and their existence supported by govemment and cause of high growth in amount. This study tries to find role model of islamic financial cooperative (BMT) in bandung city, Indonesia. This study was meant to be explanatory, using case study to explain factors that crating marketing effectiveness and marketing metrics taht can be implemented effectiveness theory, as for marketng metrics proposed to be used as a measurement; based on Hoolvey&Lynch (1984),Ambler(2004). Marketing effectiveness in this study viewed as ability of organization to attain their objectives, how was the process of marketing effectiveness achieved in Islamic financial cooperative. The factors of marketng effectiveness used was proposed by Carson, which are : limitations of marketing expenditure, marketing expertise, and marketing impact; Marketng planning vs. operation, levels of generalization, marketin planning adapted to small firm, stages of marketing, level of activity. This study academically open up conditions of marketing effectiveness in Islamic financial cooperative that rarly explore